2021
DOI: 10.3390/ma14092366
|View full text |Cite
|
Sign up to set email alerts
|

Computer Aided Design Modelling and Finite Element Analysis of Premolar Proximal Cavities Restored with Resin Composites

Abstract: This study evaluated the stress distribution in five different class II cavities of premolar models restored with conventional or bulk-fill flowable composite by means of finite element analysis (FEA) under shrinkage and occlusal loading. An upper validated premolar model was imported in the software, and five class II cavities with different occlusal extensions and dimensions were prepared: horizontal cavity on the mesial surface (horizontal slot), mesio-occlusal cavity, mesial cavity (vertical slot), tunnel … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
22
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 17 publications
(22 citation statements)
references
References 37 publications
0
22
0
Order By: Relevance
“…Furthermore, the results were not calculated considering data deviation or systematic error which can be present in biological tissues and complex systems. 13 Despite limitations, the present study assists clinicians in selecting the appropriate composite resin when an improved mechanical response is needed. 6 …”
Section: Discussionmentioning
confidence: 94%
“…Furthermore, the results were not calculated considering data deviation or systematic error which can be present in biological tissues and complex systems. 13 Despite limitations, the present study assists clinicians in selecting the appropriate composite resin when an improved mechanical response is needed. 6 …”
Section: Discussionmentioning
confidence: 94%
“…Initially, the endodontically treated teeth would be subject to different temperature cycles and pH variation in the oral cavity. In addition, the simulated materials would present some defects that are not simulated in isotropic structures [ 41 ]. There are, possible influences of oblique loading, sliding contacts and operator errors that are simplified [ 42 ].…”
Section: Discussionmentioning
confidence: 99%
“…Biomaterials that possess adequate compressive and tensile strength and relatively low elastic modulus could act as a cushion layer to the shrinkage stress transmitted to the tooth tissues [21]. However, in adhesive restorations, the mechanical behavior under compressive loading and shrinkage stress can be associated with several factors other than the material, including the enamel and dentine volumes lost [4]. In this study, the highest Elastic modulus mean value was observed for Grandio (22.15 ± 2.68 GPa) and the lowest for 4 Seasons (10.06 ± 1.37 GPa), as observed in Table 5.…”
Section: Discussionmentioning
confidence: 99%
“…The main challenge of developing these materials is to provide an effective bond strength to the hard tissues, such as enamel and dentin, as well as lower or no polymerization shrinkage [1,2]. In addition, the mechanical and chemical properties of these materials have been improved along the years [1][2][3][4], positively affecting their clinical performance. The aesthetic restorative technique has also been improved, which increases the longevity of the resin-based restorations, especially for posterior teeth [4][5][6].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation